Trends and research user intent as a satisfaction in using online food delivery app a bibliometric analysis - Krishnamoorthi, Thiban; Azman, Norhidayah (Edelweiss Applied Science and Technology, 2026)
Consumer eating habits have changed as a result of the quick development of food delivery services, especially in emerging nations. The purpose of this study is to methodically investigate topic developments and research trends related to client satisfaction with online food delivery services. Sixty-three Scopus-indexed journal articles published between 2017 and 2025 were examined using Biblioshiny and VOSviewer. Performance analysis and scientific mapping approaches identified prominent authors, top journals, productive nations, cooperation networks, and emerging research topics. The results show a consistent increase in academic interest, with Portugal exhibiting the highest citation impact, while India and Malaysia contributed the most papers. Major study subjects include customer satisfaction, website quality, service quality, convenience, price, and the impact of COVID-19. E-service quality has become the most prevalent and rapidly developing topic. User experience optimization and digital service excellence are increasingly important in customer satisfaction research within online food delivery services. The findings have significant implications for practitioners by emphasizing the strategic importance of website quality, service efficiency, and convenience in enhancing customer satisfaction and maintaining competitiveness. For researchers, the results highlight research gaps and suggest future directions.